A Review on Pleasure-driven Eating: Unravelling the Role of Hedonic Hunger in Modern Diets and Health - Prasun Roychowdhury; Poulamee Ghosh; Moumita Chatterjee; Shibani Lahiri (Current Functional Foods, 2026)
Introduction: Hedonic hunger describes an appetite driven by the desire for pleas-urable eating experiences, distinct from the body's need for energy and nutrients (physiolog-ical hunger). This review examines the scientific underpinnings of hedonic hunger, including the research methodologies used to monitor it, the factors that influence it, the molecular mechanisms, physiological consequences, and implications for public health. Methods: This review article was developed by synthesizing insights from research pub-lished in ScienceDirect, Web of Science, JSTOR, PubMed, Scopus, and Google Scholar, primarily covering studies from the past 25 years. The selection criteria included research papers focusing on hedonic hunger, obesity, eating disorders, and the neurobiological and physiological mechanisms underlying hunger regulation. Results and Discussion: In contrast to physiological hunger, which is essential for survival, hedonic hunger can lead to excessive calorie consumption and subsequent weight gain. The brain's reward system plays a central role, triggering the release of dopamine in response to food cues. Other hormones, such as ghrelin, leptin, enkephalins, endorphins, neuropeptide Y, agouti-related protein, melanocortin-4, and gut microbes, may also contribute. Environmental and individ-ual factors, including the availability of high-calorie foods, stress, and sleep deprivation, fur-ther influence hedonic hunger. Conclusion: Understanding the mechanisms and consequences of hedonic hunger is crucial for developing public health strategies to combat the obesity epidemic. Further research is needed to refine methodologies, assess its prevalence in various populations, unravel the intricate mechanisms and influencing factors, evaluate potential biomarkers, and determine its implications for clinical practice.